إجراءات الطعن في قرارات مجلس المنافسة - بريك, ريم; وطوط, هناء; باهي, إيمان (University of Eloued جامعة الوادي, 2023)
يعد مجلس المنافسة سلطة ادارية مستقلة، كلفه المشرع بموجب الامر03/03 المتعلق بالمنافسة بمهمة تنظيم السوق، فله صلاحية اصدار قرارات تنفيذية تتعلق اما بكل ما يخص الرقابة على الممارسات المقيدة (المنافية) للمنافسة، او بعمليات التجميع الاقتصادي، ونص على امكانية الطعن في قراراته امام الجهات القضائية. لكن مع ذلك توجد العديد من الاشكالات وذلك لما قيد المشرع وميز بين الطعون ففي الطعن في القرارات المتعلقة بالممارسات المقيدة للمنافسة خص المشرع حق الطعن فيها لأطراف الخصومة فقط دون الغير ولم يخول لهذا الاخير حق التدخل في الدعوى، وتوجه هذه الطعون الاخيرة امام الغرفة التجارية لمجلس قضاء الجزائر. وكذلك في قرارات الترخيص بالتجميع الاقتصادي خص المشرع حق الطعن للمؤسسة صاحبة الطلب وفي قرارات الرفض فقط، ويوجه هذا الطعن امام مجلس الدولة. The Competition Council is an independent administrative authority, assigned by the legislator under Order 03/03 related to competition with the task of regulating the market. Judicial authorities. However, there are many problems due to the fact that the legislator restricted and distinguished between appeals. In appealing to decisions related to practices that restrict competition, the legislator singled out the right to appeal to the litigating parties only, and did not give the latter the right to intervene in the case. These last appeals are addressed before the Chamber of Commerce of the Council of Ministers. Algeria district. Likewise, in decisions licensing economic pooling, the legislator allocated the right of appeal to the requesting institution and in rejection decisions only, and this appeal is directed before the State Council.
مذكرة ماستر
Keywords: مجلس المنافسة، قرارات مجلس المنافسة، الطعن في قرارات مجلس المنافسة، الممارسات المقيدة للمنافسة، التجميع الاقتصادية; Competition Council, Competition Council decisions, appeal against Competition Council decisions, practices restricting competition, economic aggregation.